Structural Rigidification of N-Aryl-pyrroles into Indoles Active against Intracellular and Drug-Resistant Mycobacteria - Semenya, Dorothy; Touitou, Meir; Ribeiro, Camila Maringolo [UNESP]; Pavan, Fernando Rogerio [UNESP]; Pisano, Luca; Singh, Vinayak; Chibale, Kelly; Bano, Georg; Toscani, Anita; Manetti, Fabrizio; Gianibbi, Beatrice; Castagnolo, Daniele (American Chemical Society (ACS), 2022)
A series of indolyl-3-methyleneamines incorporating lipophilic side chains were designed through a structural rigidification approach and synthesized for investigation as new chemical entities against Mycobacterium tuberculosis (Mtb). The screening led to the identification of a 6-chloroindole analogue 7j bearing an N-octyl chain and a cycloheptyl moiety, which displayed potent in vitro activity against laboratory and clinical Mtb strains, including a pre-extensively drug-resistant (pre-XDR) isolate. 7j also demonstrated a marked ability to restrict the intracellular growth of Mtb in murine macrophages. Further assays geared toward mechanism of action elucidation have thus far ruled out the involvement of various known promiscuous targets, thereby suggesting that the new indole 7j may inhibit Mtb via a unique mechanism.
Keywords: Antimicrobial resistance; Indole; MDR-TB; Pyrrole; Tuberculosis; XDR-TB